5(x+1)=6

Simple and best practice solution for 5(x+1)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+1)=6 equation:


Simplifying
5(x + 1) = 6

Reorder the terms:
5(1 + x) = 6
(1 * 5 + x * 5) = 6
(5 + 5x) = 6

Solving
5 + 5x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 5x = 6 + -5

Combine like terms: 5 + -5 = 0
0 + 5x = 6 + -5
5x = 6 + -5

Combine like terms: 6 + -5 = 1
5x = 1

Divide each side by '5'.
x = 0.2

Simplifying
x = 0.2

See similar equations:

| 4(-r+1)+1=-r+29 | | 31+1d=65 | | 31+1d=50 | | (4x^2+3x-1)-(x^2-6x+8)= | | 3x=3x-21 | | 31+1d=12 | | 4x=9-x | | (x-1)(x+3)=4 | | 167=6+7(2-7x) | | ln(2x+1)+ln(x-1)=lnx | | 0.0058x^2-0.67x+15.2=-3 | | 36i^2+16i+36=0 | | (2x)(x+2)=52 | | z^2-6iz-9+4i=0 | | f(x)=2x^2-8x-1 | | 525.00+0.21x+585.00+0.13x= | | 7ln(2x)=21 | | 9x(x-8)=y-3 | | 5+1z=17 | | 8(3)=4(x-1) | | -0.9x-0.6(2)=2.3 | | p(x)=3x^3+32x^2+32x+27 | | -0.9(2)-0.6y=2.3 | | x-0.4x=186 | | 9x-2(1)=-37 | | 9(1)-2y=-37 | | 4+2y-2=8y+9-5y | | 3(x-3)=5(1.5x+x) | | 27x^2+32x=52 | | 5y=-x | | -2(1)+12y=47 | | 3r-q=2 |

Equations solver categories